Vaginal Length After Laparoscopic Hysterectomy: Laparoscopic Versus Vaginal Closure. Randomized Trial Update [39B]. (May 2017) - Nezhat, Camran; Main, Jillian; Falik, Rebecca; Di Francesco, Lucia; Farrimond, Frances; Nezhat, Azadeh
Abstract : INTRODUCTION: The purpose of our study is to observe the change in vaginal length after total laparoscopic hysterectomy with laparoscopic cuff closure (LC) versus vaginal approach to cuff closure (VC). METHODS: This is an update on our prospective, randomized study of women undergoing total laparoscopic hysterectomy. Vaginal length was measured pre-operatively and at 6-12 weeks, 6 months and then 12 months postoperatively. RESULTS: A total of 76 patients were included in the study (37 women in the vaginal group, 39 women in the laparoscopic group). The median preoperative vaginal lengths were not statistically significant: VC 10.7cm vs LC 11.8 cm; (P=.31). The difference in median vaginal lengths at 6-12 weeks were: VC 9.8cm versus LC 9.7 cm (P=.92). The median vaginal lengths at 6 months were 10.5cm in the VC and 10.2cm in the LC (P=.63). The median vaginal lengths at 12 months were 11.0 cm in the VC and 11.2 cm in the LC (P=.65). The cuff closure time was significantly longer in the LC group (15.6 min versus 7.9 minutes in the VC, P < .05). There were zero cases of vaginal cuff dehiscence. 13.5% of women in the VC group developed granulation tissue vs 2.5 % in the LC group (P < .05). CONCLUSION: Vaginal length at 6 and 12 months did not differ based on method of vaginal closure. Laparoscopic closure times are longer than vaginal cuff closures and neither method had cases of vaginal cuff dehiscence. Vaginal closure is associated with an increased risk of developing granulation tissue.